Characterization of interactions between a metabolic uncoupler O-chlorophenol and extracellular polymeric substances of activated sludge. (April 2019) - Fang, Fang; Xu, Run-Ze; Wang, Su-Na; Zhang, Lu-Lu; Huang, Yan-Qiu; Luo, Jing-Yang; Feng, Qian; Cao, Jia-Shun
Abstract: Metabolic uncouplers are widely used for the in-situ reduction of excess sludge from activated sludge systems. However, the interaction mechanism between the metabolic uncouplers and extracellular polymeric substances (EPS) of activated sludge is unknown yet. In this study, the interactions between a typical metabolic uncoupler, o-chlorophenol (oCP), and the EPS extracted from activated sludge were explored using a suite of spectral methods. The binding constants calculated for the four peaks of three-dimensional excitation-emission matrix fluorescence were in a range of 1.24–1.76 × 10 3  L/mol, implying that the tyrosine protein-like substances governed the oCP-EPS interactions. Furthermore, the results of Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy and 1 H nuclear magnetic resonance indicated that the carboxyl, carbonyl, amine, and hydroxyl groups of EPS were the main functional groups involved in the formation of the oCP-EPS complex. The results of this study are useful for understanding the interactions between metabolic uncouplers and the EPS of activated sludge as well as their fates in biological wastewater treatment systems. Graphical abstract: Image 1 Highlights: The interaction mechanism between oCP and EPS of activated sludge was explored. The oCP-EPS interaction was mainly governed by the tyrosine protein-like substances. Carboxyl, carbonyl, amine, and hydroxyl groups of EPS were the main interaction groups. Abstract : The interaction mechanisms between metabolic uncouplers and EPS of activated sludge were elucidated using a suite of spectral methods.